Personal Taxation of Capital Income and the Financial Leverage of Firms - Frank M. Fossen; Martin Simmler (International Tax and Public Finance, 2016)
Tax competition for capital has led to a trend where many countries levy lower taxes on interest income, often introducing differential taxation between interest and business income. This study analyzes the effect on firm debt usage. We exploit Germany's 2009 tax reform, which introduced a final withholding tax on interest income with a flat rate 18 percentage points below the unchanged tax rate on income from unincorporated businesses, as a quasi-experiment. The results, based on firm-level panel data, indicate that firms increase their leverage when the tax rate on interest income decreases, albeit to a small degree.
Additional information: The final publication is available at Springer via http://dx.doi.org/10.1007/s10797-015-9349-0.
Keywords: H25; H24; G32; 330; Income taxation; Capital taxation; Financial structure; Leverage; Matching